Alpha7 acetylcholine receptor autoantibodies are rare in sera of patients diagnosed with schizophrenia or bipolar disorder - Hoffmann, Carolin (PLoS One, 2018)
The α7 acetylcholine receptor (AChR) has been linked with the onset of psychotic symptoms and we hypothesized therefore that it might also be an autoimmune target. Here, we describe a new radioimmunoassay (RIA) using iodine 125-labelled α-bungarotoxin and membrane extract from transfected HEK293 cells expressing human α7 AChR. This RIA was used to analyze sera pertaining to a cohort of 711 subjects, comprising 368 patients diagnosed with schizophrenia spectrum disorders, 140 with bipolar disorder, 58 individuals diagnosed of other mental disorders, and 118 healthy comparison subjects. We identified one patient whose serum tested positive although with very low levels (0.2 nM) for α7 AChR-specific antibodies by RIA. Three out of 711 sera contained antibodies against iodine 125-labelled α-bungarotoxin, because they precipitated with it in the absence of α7 AChR. This first evidence suggests that autoantibodies against α7 AChR are absent or very rare in these clinical groups.